EPSA Philosophy of Science: Amsterdam 2009
XIV, 458 p.
Keywords: This is a collection of high-quality research papers in the philosophy of science, deriving from papers presented at the second meeting of the European Philosophy of Science Association in Amsterdam, October 2009.